2018
DOI: 10.1002/osp4.278
|View full text |Cite
|
Sign up to set email alerts
|

Effects of consuming a high‐protein diet with or without soy protein during weight loss and maintenance: a non‐inferiority, randomized clinical efficacy trial

Abstract: SummaryObjectiveThis 12‐month randomized, non‐inferiority clinical trial sought to determine the impact of consuming soy protein as part of an energy‐restricted, high‐protein diet on weight loss, body composition and cardiometabolic health.MethodsSeventy‐one adults (58 female) with overweight or obesity (body mass index: 32.9 ± 3.6 kg m−2) were randomly assigned to consume three servings of soy (S) or non‐soy (NS) protein foods per day for 12 months. All participants completed a group‐based behavioural weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…( 84 ). These findings align with other research, which indicates there is little evidence suggesting one source of protein is more effective than another as an aid for weight management ( 85 89 ).…”
Section: Soyfoods Overviewsupporting
confidence: 89%
“…( 84 ). These findings align with other research, which indicates there is little evidence suggesting one source of protein is more effective than another as an aid for weight management ( 85 89 ).…”
Section: Soyfoods Overviewsupporting
confidence: 89%
“…In 58 obese adults (82% women; mean baseline age 42 years and BMI of 33) consuming energy-restricted low fat and high protein diets including three servings/day of soy protein or non-soy protein foods in a group-based weight loss program for four months showed that soy and non-soy protein had similar effects on body weight and fat loss and maintenance (4–12 months) [ 62 ].…”
Section: Observational Studiesmentioning
confidence: 99%
“…In recent years, the beneficial effect of soy products on body weight has aroused the interest in the scientists [17,18,19], whose biological effects in preventing metabolic disorders such as hyperlipidemia, cardiovascular disease and type 2 diabetes mellitus were commended [20]. Soy products herein refers to soy and a food processed from soy, and is mainly composed of soy protein, soy isoflavone and soy fiber, such as soy milk, soy shakes and so on.…”
Section: Introductionmentioning
confidence: 99%